Respuesta :
We simplify the equation to the form, which is simple to understand
5(3+k)=45
Reorder the terms in parentheses
+(+15+5k)=45
Remove unnecessary parentheses
+15+5k=+45
We move all terms containing k to the left and all other terms to the right.
+5k=+45-15
We simplify left and right side of the equation.
+5k=+30
We divide both sides of the equation by 5 to get k.
k=6
5(3+k)=45
Reorder the terms in parentheses
+(+15+5k)=45
Remove unnecessary parentheses
+15+5k=+45
We move all terms containing k to the left and all other terms to the right.
+5k=+45-15
We simplify left and right side of the equation.
+5k=+30
We divide both sides of the equation by 5 to get k.
k=6